Lightweight aggregate fiber reinforced concrete treated by doping granulation technology and preparation method of lightweight aggregate fiber reinforced concrete

Through the granulation technology, iron tailings sand, gold tailings sand and high alumina cement are processed to form spherical particles with high strength and are used in light aggregate fiber reinforced concrete, which solves the problem of solid waste in the concrete in the prior art. The problem of effectively playing the role of the skeleton has achieved high-performance and low-cost concrete preparation, which meets the requirements of sustainable development.

CN119390407APending Publication Date: 2025-02-07HOHAI UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411411651.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

When existing light aggregate fiber reinforced concrete uses solid waste such as iron tailings sand and gold tailings sand, it cannot effectively play the role of the skeleton when it is directly added to the concrete, resulting in the difficulty of the concrete performance to meet the requirements.

Method used

Use granulation technology to treat iron tailings sand, gold tailings sand and high alumina cement to form spherical particles, and use alkali soaking to improve the strength and density of the particles. Use light aggregate to replace traditional ceramic granules, and reasonably prepare concrete raw materials to Reduce production costs.

Benefits of technology

On the premise of ensuring the mechanical properties of concrete, production costs are reduced, solid waste emissions are reduced, and environmental pollution is reduced. The concrete has low density and high mechanical properties, which meets the requirements of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390407A_ABST
    Figure CN119390407A_ABST
Patent Text Reader

Abstract

The invention discloses lightweight aggregate fiber reinforced concrete treated by a doping granulation technology and a preparation method thereof, and the concrete per unit volume is prepared from the following components: 600-650 parts of cement, 90-105 parts of fly ash, 140-160 parts of silica fume, 140-160 parts of slag powder, 1000-1200 parts of lightweight aggregate, 8-12 parts of a water reducing agent, 165-180 parts of water and 100-180 parts of mixed fiber, and the water-cement ratio is 0.2-0.35. The lightweight aggregate is spherical particles obtained by treating iron tailing sand, gold tailing sand and high-alumina cement through a granulation technology. The spherical particles are soaked in an alkaline solution for 2-4 hours, and after soaking is finished, the spherical particles are taken out and dried for 12-24 hours to form the lightweight aggregate. Pores in the surface are filled with the reaction product, so that the strength of the lightweight aggregate is improved while the water absorption is reduced, the concrete is low in density and high in mechanical property, the discharge of solid wastes is reduced, and the cost is also reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of concrete materials, and in particular relates to a lightweight aggregate fiber reinforced concrete processed by granulation technology and a preparation method thereof. Background Art

[0002] At present, with the rapid development of high-grade highway traffic modernization, the development of concrete roads has been placed in an important position in road construction. With the rapid development of society and economy, people have higher and higher requirements on the performance of concrete. Ordinary concrete has limited its development due to its defects such as heavy weight, low tensile capacity and poor crack resistance. Therefore, people continue to improve the performance of concrete materials according to the use needs, so that the strength and other properties of concrete are continuously improved.

[0003] Taking into account the requirements of project cost and construction period, lightweight aggregate fiber reinforced concrete is usually used, which has good mechanical properties while reducing its own weight. Clay ceramsite and shale ceramsite are often used as lightweight aggregate to prepare lightweight aggregate concrete, but the resources of clay and shale are limited.

[0004] In lightweight aggregate fiber reinforced concrete, solid wastes such as iron tailings and gold tailings are used. After being processed by granulation technology, lightweight aggregate is obtained to replace clay ceramsite, shale ceramsite, etc., which can reduce the emission of solid waste and reduce costs at the same time.

[0005] The prior art discloses a lightweight aggregate concrete, which is made of the following raw materials: 410-450 parts of cement, 45-50 parts of fly ash, 510-540 parts of ceramsite, 650-750 parts of sand and gravel, 2.45-2.58 parts of admixture, 169-200 parts of water and 34-36 parts of reinforcing fiber. The preparation method of the ultra-high performance iron tailings sand concrete comprises the following steps: (1) polycarboxylic acid high-performance water reducer, polycarboxylic acid slump retainer, polymer water retainer, sodium gluconate and sodium dodecyl sulfate are mixed in proportion and then water is added and stirred to obtain an admixture dispersion; (2) cement, fly ash, ceramsite, natural sand, water, fiber and admixture dispersion are mixed and stirred to obtain lightweight aggregate concrete. In this technology, ceramsite and natural sand are used as lightweight aggregate, which are expensive and have limited resources; the ceramsite used has high water absorption, which is not conducive to concrete molding.

[0006] CN105236860A discloses an iron tailings mixed sand concrete, which is composed of 52.5 grade cement, iron tailings mixed sand, crushed stone, admixture, polycarboxylic acid high-efficiency water reducing agent and water; CN108191319A discloses an iron tailings sand concrete and a preparation method thereof, the concrete is made of the following raw materials in parts by weight: 20-40 parts of tailings balls, 10-20 parts of tailings powder, 5-15 parts of cement, and 2-6 parts of water; the tailings balls are made of the following raw materials in parts by weight: 8-12 parts of cement, 36-48 parts of tailings powder, 17.6-24 parts of water, 1.6-2.4 parts of water reducing agent, and 0.24-0.36 parts of rubber powder. The preparation method includes the preparation of tailings balls and the preparation of concrete. The concrete uses iron tailings sand as raw material, reuses waste, and reduces the pollution of tailings to the environment. The preparation method is simple, and the obtained concrete has high strength. The tailings balls are used as aggregates, and the strength of the obtained concrete is greater than the strength of the aggregates. The concrete is studied from a microscopic perspective, and the concrete is highly practical. CN105036621A discloses a high-strength concrete made of ultra-fine iron tailings mixed sand, which is composed of 52.5-grade cement, iron tailings mixed sand, crushed stone, admixture, polycarboxylic acid high-efficiency water reducing agent for concrete and water; CN105236895A discloses a high-performance gold tailings sand concrete, which is prepared from the following components in parts by weight: 425-465 parts of silicate cement, 635-645 parts of gold tailings sand, 860-960 parts of crushed stone with a particle size of 5-20 mm, 100-180 parts of river sand, 30-146 parts of fly ash, 50-90 parts of silica fume, 23-57 parts of basalt fiber, 32-88 parts of straw powder, 3-7 parts of water reducing agent, 25-85 parts of inorganic nanoparticles, 6-18 parts of nano calcium carbonate, 40-100 parts of acrylic emulsion, 148-162 parts of CFRP tendons, and 15-2 0 parts, 10-15 parts of chemical resistance modifier, 10-85 parts of carbon nanotubes, and 185-300 parts of water, the components of which are complex and the cost is high; CN113773014A discloses a gold tailings concrete and a preparation method thereof, the gold tailings concrete is prepared from the following raw materials: cement, slag powder, fly ash, mixed sand, fine stone, crushed stone, water, and water reducer; the mixed sand is composed of the following components in weight percentage: 20-30% of gold tailings sand or hydrophobically modified gold tailings sand, and 70-80% of river sand; cement, slag powder, fly ash, river sand, fine stone and crushed stone are mixed and stirred to obtain a solid mixture; water and the remaining raw materials except the gold tailings sand are added to the solid mixture, and stirred to obtain concrete slurry; finally, the gold tailings sand or hydrophobically modified gold tailings sand is added to the concrete slurry, and stirred to obtain concrete, in which the gold tailings sand needs to be hydrophobically modified, and the process is complicated. In the above technologies, iron tailings or gold tailings are used as concrete mineral admixtures. Although the iron tailings and gold tailings can be effectively utilized, they cannot play a better skeleton role when directly added to concrete, resulting in the performance of the obtained concrete being difficult to meet the requirements. Summary of the invention

[0007] The object of the present invention is to provide a lightweight aggregate fiber reinforced concrete treated by granulation technology. The lightweight aggregate fiber reinforced concrete uses solid waste iron tailings, gold tailings and high-alumina cement as aggregates, is treated by granulation technology, and has a lower production cost while ensuring its mechanical properties.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The invention discloses a lightweight aggregate fiber reinforced concrete processed by granulation technology. The concrete is made of the following components by weight per unit volume: 600-650 parts of cement, 90-105 parts of fly ash, 140-160 parts of silica fume, 140-160 parts of slag powder, 1000-1200 parts of lightweight aggregate, 8-12 parts of water reducing agent, 165-180 parts of water, 100-180 parts of mixed fiber, and the water-cement ratio is 0.2-0.35.

[0010] The light aggregate is spherical particles obtained by granulating iron tailings sand, gold tailings sand and high-alumina cement.

[0011] The lightweight aggregate is obtained by treating iron tailings sand, gold tailings sand and high-alumina cement by granulation technology to form spherical particles and then soaking them in alkali.

[0012] Preferably, the lightweight aggregate is spherical particles with a uniform particle size of 4-10 mm obtained by dry granulation technology and screening.

[0013] Furthermore, the spherical particles are obtained by mixing iron tailings, gold tailings and high-alumina cement in a rotating drum through a drum granulator;

[0014] The spherical particles are obtained by granulating iron tailings, gold tailings and high alumina cement in a mass ratio of (1-2):1:(1-2); more preferably, iron tailings, gold tailings and high alumina cement are mixed in a mass ratio of 1:1:2.

[0015] Furthermore, in order to improve the strength of the spherical particles and reduce the surface pores, the particles formed in the drum granulator are soaked in an alkaline solution and then dried to form lightweight aggregate.

[0016] Preferably, the forming step of the above particles is: put iron tailings sand, gold tailings and high-alumina cement powder raw materials in a granulator, add 10%-30% water of the solid powder, and roll to form spherical particles.

[0017] More preferably, the spherical particles are immersed in an alkaline solution for 2-4 hours, and after the immersion, they are taken out and dried for 12-24 hours.

[0018] Preferably, the alkaline solution is a solution of sodium silicate and sodium hydroxide in a molar ratio of silicon dioxide to sodium oxide of 1.0-2.5.

[0019] More preferably, the lightweight aggregate is formed by soaking in a mixed alkaline solution of sodium silicate and sodium hydroxide having a nanomolar ratio of silicon dioxide to oxide of 1.5.

[0020] Iron tailings, gold tailings and high-alumina cement contain rich silicon-alumina phases, which can react with alkali. The reaction products fill the pores on the surface, reducing water absorption while increasing the strength of lightweight aggregate, making the concrete not only low in density but also high in mechanical properties.

[0021] Preferably, the cement is at least one of Portland cement and slag, and has a strength greater than or equal to 42.5 MPa.

[0022] Preferably, the calcium oxide content of the fly ash is less than 10%, and the silicon dioxide content of the silica ash is not less than 85%.

[0023] Slag powder is S95 grade mineral powder.

[0024] Preferably, the water reducing agent is a polycarboxylic acid-based high-efficiency water reducing agent, and the water reducing rate is greater than 20%.

[0025] Preferably, the mixed fiber is a uniformly mixed product of PVA fiber, PE fiber and POM fiber. The PVA fiber has a diameter of 39 μm, a length of 12 mm, an elongation at break of about 6%, an elastic modulus of about 40 GPa, and a breaking strength greater than 1600 MPa. The PE fiber has a diameter of 25 μm, a length of 6 to 18 mm, an elongation at break of no more than 3.5%, an elastic modulus of greater than 122 GPa, and a breaking strength greater than 3.1 GPa. The POM fiber has a diameter of 200 μm, a length of 12 mm, an elastic modulus of greater than 8 GPa, a breaking strength greater than 800 MPa, and an elongation at break between 16 and 20%.

[0026] The invention provides a lightweight aggregate fiber reinforced concrete processed by granulation technology, which comprises the following preparation raw materials by weight: cement, silica fume, fly ash, slag powder, lightweight aggregate, water reducing agent, water and fiber.

[0027] In the present invention, the raw materials for preparing the lightweight aggregate fiber reinforced concrete treated by the granulation technology include 600-650 parts of cement, preferably 620-649 parts of cement, by weight. In the present invention, the cement is preferably silicate cement, more preferably PO42.5 and / or PO52.5 cement, and further preferably PO42.5 cement.

[0028] In the present invention, based on the mass percentage of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 140 to 160 parts of silica fume, preferably 150 to 159 parts. In the present invention, the content of SiO2 in the silica fume is not less than 85%.

[0029] In the present invention, based on the mass fraction of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 90 to 105 parts of fly ash, preferably 100 to 104 parts.

[0030] In the present invention, based on the mass percentage of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 140 to 160 parts of slag powder, preferably 150 to 159 parts.

[0031] In the present invention, based on the mass fraction of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 1000-1200 parts of lightweight aggregate, preferably 1049 parts. In the present invention, the lightweight aggregate is preferably obtained by granulation technology and screening with a double-layer vibrating sand screener; the particle size of the lightweight aggregate after screening is preferably 4-10mm. The present invention uses a double-layer vibrating sand screener to screen the lightweight aggregate, and completely screens out the part with a particle size greater than 10mm. In the present invention, the lightweight aggregate is further preferably treated with alkali immersion.

[0032] In the present invention, based on the mass fraction of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 8 to 12 parts of water reducer, preferably 9 parts. In the present invention, the water reducer is preferably a polycarboxylic acid high-efficiency water reducer. In the present invention, the water reduction rate of the water reducer is preferably greater than or equal to 40%, more preferably 40%.

[0033] In the present invention, based on the mass fraction of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 100 to 180 parts of fiber, preferably 134 to 149 parts. In the present invention, the fiber is a uniform mixture of PVA fiber, PE fiber and POM fiber.

[0034] In the present invention, based on the mass fraction of cement, the raw materials for preparing the lightweight aggregate fiber reinforced concrete include 165 to 180 parts of water, preferably 170 to 179 parts.

[0035] The lightweight aggregate fiber reinforced concrete treated with granulation technology is preferably made of the following components, calculated by weight, per unit volume of concrete: 620-649 parts of cement, 100-104 parts of fly ash, 150-159 parts of silica fume, 150-159 parts of slag powder, 1049 parts of lightweight aggregate, 9 parts of water reducer, 170-179 parts of water, and 134-149 parts of mixed fiber.

[0036] The preparation method of concrete of the present invention is as follows Figure 1 As shown:

[0037] Preparation of lightweight aggregate:

[0038] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in proportion and add them into a drum granulator to form spherical particles with a particle size of 4-10mm;

[0039] II. Soak the above particles in an alkaline solution for 2-4 hours, and then take them out and dry them for 12-24 hours.

[0040] Concrete preparation method:

[0041] Weigh cement, silica fume, fly ash, slag powder and lightweight aggregate by weight, mix and stir in a horizontal mixer to obtain a dry mix;

[0042] Weigh a water reducer and water to obtain a first mixture; then stir and mix the dry mix and the first mixture to obtain a second mixture; stir and mix the second mixture and water to obtain a slurry until the slurry becomes fluid;

[0043] The same amount of PVA fiber, PE fiber and POM fiber are weighed and uniformly mixed, and then stirred and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0044] The invention reduces the various problems caused by tailings deposition and production and replaces the ceramsite used in traditional lightweight aggregates, reduces the production cost of concrete, reduces the discharge of tailings ponds, reduces environmental pollution, and is in line with the sustainable development supported by China in recent years. By using lightweight aggregate fiber reinforced concrete (usually prepared from cement, silica fume, fly ash, slag powder and quartz sand), a concrete with ultra-high compressive strength and durability is invented.

[0045] Beneficial effects:

[0046] 1) The present invention provides a lightweight aggregate fiber reinforced concrete, in which iron tailings sand, gold tailings sand and high-alumina cement are prepared into artificial lightweight aggregate through granulation technology, thereby reducing the emission of solid waste and also reducing the cost.

[0047] 2) The present invention provides a lightweight aggregate fiber reinforced concrete. Artificial lightweight aggregate is soaked in alkali. Iron tailings sand, gold tailings sand and high-alumina cement contain rich silicon-alumina phases and can react with alkali. The reaction products fill the pores on the surface, reducing water absorption while improving the strength of the lightweight aggregate, so that the concrete has not only low density but also high mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] Figure 1 Concrete preparation process. DETAILED DESCRIPTION

[0049] In order to further illustrate the present invention, the lightweight aggregate fiber reinforced concrete provided by the present invention is described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] In the present invention, unless otherwise specified, all preparation raw materials are preferably commercially available products well known to those skilled in the art.

[0051] Some raw material parameters in the following examples and comparative examples of the present invention are as follows:

[0052] Cement: PO42.5 cement;

[0053] Silica fume: SiO2 content greater than 85%;

[0054] Mineral powder: S95 grade;

[0055] Iron tailings: particle size ≤ 1.25mm, of which the mass content of iron tailings with particle size < 0.16mm is ≤ 25wt.%; Gold tailings: particle size ≤ 1mm;

[0056] High alumina cement: CA500-A700;

[0057] Water reducing agent: water reducing rate is 40%;

[0058] Mixed fiber: a mixed product of PVA fiber, PE fiber, and POM fiber. The diameter of PVA fiber is 39μm, the length is 12mm, the elongation at break is about 5%-7%, the elastic modulus is about 38-42GPa, and the breaking strength is greater than 1600MPa. The diameter of PE fiber is 25μm, the length is 6-18mm, the elongation at break is not more than 3.5%, the elastic modulus is greater than 122GPa, and the breaking strength is greater than 3.1GPa. The diameter of POM fiber is 200μm, the length is 12mm, the elastic modulus is greater than 8GPa, the breaking strength is greater than 800MPa, and the elongation at break is about 16%-20%.

[0059] Example 1

[0060] A lightweight aggregate fiber reinforced concrete is made of the following components, measured by weight, per unit volume of concrete: 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, 1000 parts of lightweight aggregate, 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent, 170 parts of water, 40 parts of PVA fiber, 40 parts of PE fiber, and 40 parts of POM fiber; the lightweight aggregate is spherical particles obtained by granulating iron tailings and gold tailings in a 1:1 ratio through granulation technology.

[0061] The preparation method comprises the following steps:

[0062] Ⅰ. Mix iron tailings sand and gold tailings in a ratio of 1:1 and add them into the drum granulator to form lightweight aggregate;

[0063] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0064] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0065] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0066] Example 2

[0067] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 1 in that the lightweight aggregate is processed by the following steps:

[0068] Ⅰ. Mix iron tailings and gold tailings in a ratio of 1:1 and add them into a drum granulator to form spherical particles;

[0069] II. Soak the above particles in a mixed alkaline solution of sodium silicate and sodium hydroxide with a silicon dioxide to oxide nanomolar ratio of 1.5 for 3 hours, take them out and dry them for 18 hours to form lightweight aggregate.

[0070] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0071] Weigh 9.5 parts of polycarboxylate water-reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0072] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0073] Example 3

[0074] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 1 in that the lightweight aggregate is processed by the following steps:

[0075] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in a ratio of 1:1:1 and add them into a drum granulator to form spherical particles;

[0076] II. The above particles are soaked in a mixed alkaline solution of sodium silicate and sodium hydroxide with a silicon dioxide to oxide nanomolar ratio of 1.5 for 3 hours. After the soaking, they are taken out and dried for 18 hours to form lightweight aggregate.

[0077] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0078] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0079] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0080] Example 4

[0081] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 1 in that the lightweight aggregate is processed by the following steps:

[0082] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in a ratio of 1:1:2 and add them into a drum granulator to form spherical particles;

[0083] II. The spherical particles are soaked in a mixed alkaline solution of sodium silicate and sodium hydroxide with a nanomolar ratio of silicon dioxide to oxide of 1.5 for 3 hours. After the soaking, they are taken out and dried for 18 hours to form lightweight aggregate.

[0084] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0085] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0086] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0087] Example 5

[0088] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 1 in that the lightweight aggregate is processed by the following steps:

[0089] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in a ratio of 1:1:2 and add them into a drum granulator to form spherical particles;

[0090] II. The spherical particles are soaked in a mixed alkaline solution of sodium silicate and sodium hydroxide with a nanomolar ratio of silicon dioxide to oxide of 1.0 for 3 hours. After the soaking, they are taken out and dried for 18 hours to form lightweight aggregate.

[0091] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0092] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0093] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0094] Example 6

[0095] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 1 in that the lightweight aggregate is processed by the following steps:

[0096] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in a ratio of 1:1:2 and add them into a drum granulator to form spherical particles;

[0097] II. The spherical particles are soaked in a mixed alkaline solution of sodium silicate and sodium hydroxide with a silicon dioxide to oxide nanomolar ratio of 2.0 for 3 hours. After the soaking, they are taken out and dried for 18 hours to form lightweight aggregate.

[0098] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0099] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0100] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0101] Control group 1

[0102] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 4 in that the lightweight aggregate is processed by the following steps:

[0103] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in a ratio of 1:1:2 and add them into a drum granulator to form spherical particles;

[0104] II. The spherical particles are soaked in a mixed alkaline solution of sodium silicate and sodium hydroxide with a nanomolar ratio of silicon dioxide to oxide of 3.0 for 3 hours. After the soaking, they are taken out and dried for 18 hours to form lightweight aggregate.

[0105] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0106] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0107] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0108] Control group 2

[0109] A method for preparing lightweight aggregate fiber reinforced concrete, which is different from Example 4 in that the lightweight aggregate is processed by the following steps:

[0110] Ⅰ. Mix iron ore tailings, gold tailings and high alumina cement in a ratio of 1:1:2 and add them into a drum granulator to form spherical particles;

[0111] II. The spherical particles are soaked in a mixed alkaline solution of sodium silicate and sodium hydroxide with a nanomolar ratio of silicon dioxide to oxide of 0.5 to form a lightweight aggregate.

[0112] Weigh 600 parts of cement, 150 parts of silica fume, 100 parts of fly ash, 150 parts of slag powder, and 1000 parts of lightweight aggregate by mass, and mix and stir in a horizontal mixer to obtain a dry mix;

[0113] Weigh 9.5 parts of polycarboxylic acid-based high-efficiency water reducing agent and 85 parts of water to mix to obtain a first mixture; then stir and mix the dry mixture and the first mixture to obtain a second mixture; stir and mix the second mixture and 85 parts of water to obtain a slurry until the slurry becomes fluid;

[0114] 40 parts of PVA fiber, PE fiber and POM fiber were weighed and mixed with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

[0115] The lightweight aggregate fiber reinforced concrete prepared in Examples 1 to 6 and Control Group 1-2 was poured into a mold, demolded after curing at room temperature for 1 day, and placed in a high-temperature steam curing box at 80°C for 2 days of steam curing. After that, the lightweight aggregate strength, lightweight aggregate water absorption, concrete strength, and concrete density were tested. The test results are shown in Table 1.

[0116]

[0117] As can be seen from Table 1, the lightweight aggregate fiber reinforced concrete prepared in Examples 1 to 6 without natron and without high-aluminum cement has very low strength of lightweight aggregate, high water absorption, and low concrete strength. When natron is added without high-aluminum cement, the lightweight aggregate has high strength, low water absorption, high concrete strength, and high density. In the example where natron is added with high-aluminum cement, the lightweight aggregate has high strength, medium water absorption, high concrete strength, and low density. As the content of high-aluminum cement increases, the strength of concrete increases and the density decreases. The higher the natron modulus, the better. The example with a natron modulus of 1.5 (Example 4) has the highest strength and the lowest density. When the natron modulus is 0.5 or 3.0, the strength of the lightweight aggregate decreases significantly, so the recommended modulus range is 1.0-2.5.

[0118] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A lightweight aggregate fiber reinforced concrete treated by granulation technology, characterized in that: Per unit volume of concrete by weight, it is made of the following components: 600 - 650 parts of cement, 90 - 105 parts of fly ash, 140 - 160 parts of silica fume, 140 - 160 parts of slag powder, 1000 - 1200 parts of lightweight aggregate, 8 - 12 parts of water reducing agent, 165 - 180 parts of water, 100 - 180 parts of mixed fiber, water-cement ratio is 0.2 - 0.35, and the lightweight aggregate is spherical particles obtained by granulation technology from iron tailings sand, gold tailings sand and high alumina cement.

2. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 1 is characterized in that: The mass ratio of iron tailings sand, gold tailings sand and high alumina cement in the spherical particles is (1 - 2):1:(1 - 2).

3. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 1, characterized in that: The particle size of the spherical particles is 4 - 10 mm.

4. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 1, characterized in that: The mixed fiber is a product of uniform mixing of any two or more of PVA fiber, PE fiber and POM fiber.

5. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 1, characterized in that: The cement is at least one of portland cement and slag, and the water reducing agent is a polycarboxylate-based superplasticizer with a water reducing rate greater than 20%.

6. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 1, characterized in that: The spherical particles are immersed in an alkali solution for 2 - 4 hours, and after soaking, they are taken out and dried for 12 - 24 hours to form lightweight aggregate.

7. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 6, characterized in that: The alkali solution is a mixed solution of sodium silicate and sodium hydroxide, and sodium silicate and sodium hydroxide are mixed according to the molar ratio of silicon dioxide to sodium oxide of 1.0 - 2.

5.

8. The lightweight aggregate fiber reinforced concrete processed by granulation technology according to claim 7, characterized in that: In the alkali solution, sodium silicate and sodium hydroxide are mixed according to the molar ratio of silicon dioxide to sodium oxide of 1.

5.

9. The method for preparing lightweight aggregate fiber reinforced concrete according to any one of claims 1 to 7, characterized in that: It includes the following steps: 1). Weigh cement, silica fume, fly ash, slag powder and lightweight aggregate and mix and stir them in a horizontal mixer to obtain a dry mix. 2). Weigh the water reducing agent and water and mix them to obtain a first mixture; then stir and mix the dry mix and the first mixture to obtain a second mixture; stir and mix the second mixture and water to obtain a slurry until the slurry shows a flowing state. 3). Stir and mix the mixed fiber with the above slurry to obtain a lightweight aggregate fiber reinforced concrete.

10. The method for preparing lightweight aggregate fiber reinforced concrete according to claim 9, characterized in that: The preparation method of the lightweight aggregate is as follows: Ⅰ. Mix iron tailings sand, gold tailings and high alumina cement in proportion and add them to a drum granulator to form spherical particles; the particle size is 4 - 10 mm. Ⅱ. Immerse the above particles in an alkali solution for 2 - 4 hours, and after soaking, take them out and dry for 12 - 24 hours.

Citation Information

Patent Citations

  • High-strength superfine iron tailing mixed sand concrete

    CN105036621A

  • Iron tailings mixing sand concrete

    CN105236860A

  • High-performance gold tailing sand concrete

    CN105236895A

  • Iron tailing sand concrete and preparation method thereof

    CN108191319A

  • Gold tailing concrete and preparation method thereof

    CN113773014A